2005
DOI: 10.1111/j.1600-0404.2005.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Further considerations on the distribution of multiple sclerosis in Sweden

Abstract: Though the epidemiologic sources are quite different, they are internally consistent and thus provide three consecutive cross-sectional views of the distribution over time. When considered together the data may be compatible with a thesis of the origin and spread of MS within Sweden from the south-central inland lake regions of the country. Such spread within a half century is too rapid for a genetic cause, including HLA patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
4
8
0
1
Order By: Relevance
“…The peak in the age-specific incidence rate was found around the ages 45-49 years and the peak in the mortality rate (not shown) was found in the age range 70-74 years. The interval between these two peaks was 25 years, which is in accord with earlier studies in Sweden [19]. In the present study, a higher incidence rate was observed among women aged 45-49, with a sex ratio (female/male) of 2.3, which is in agreement with previous studies [20].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The peak in the age-specific incidence rate was found around the ages 45-49 years and the peak in the mortality rate (not shown) was found in the age range 70-74 years. The interval between these two peaks was 25 years, which is in accord with earlier studies in Sweden [19]. In the present study, a higher incidence rate was observed among women aged 45-49, with a sex ratio (female/male) of 2.3, which is in agreement with previous studies [20].…”
Section: Discussionsupporting
confidence: 95%
“…The county of Värmland had the highest disability and mortality rates from MS [22]. The highest hospitalization rates were found in the county of Uppsala [19]. The present results are partly consistent with those of earlier studies, where the rates of MS followed a latitude gradient that increased from southern to northern Sweden [22].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding, i.e. the great variation of MS rates within the county, was detected by us before and was interpreted as an indication of diffusion [20,31].…”
Section: Discussionmentioning
confidence: 79%
“…In Norway, the first diagnoses of MS in Sami people were made in the early 1990s, and the lowest incidence of MS was found in the most northerly county, Finnmark, where the Sami population is highest [59] . Genetic admixture may confer protection also in non-Sami in the northern parts of Norway and Sweden, where the MS prevalence is lower than expected by latitude, given the decreasing north-to-south gradient that is observed across Europe [10,12,60] . Still, we find a protective association with UVR exposure and possibly also cod liver oil intake in this population [12] .…”
Section: Ms Susceptibility Genesmentioning
confidence: 99%